The relationship of salesmanship personality towards sales performance / Aronick Edward Majimbun - Majimbun, Edward Aronick (2013)
The purpose of this study is to know whether there is a relationship between salesmanship personalities towards the sales performance. The personality comes from the Big Five Model which is the Openness, Conscientiousness Extraversion Agreeableness and Neuroticism". This study has been further discussed by some previous researcher to investigate the relationship between salesmanship personalities that affect or impact towards sales performance. Apart from that, this research is generally conducted within Bina Puri Construction Sdn Bhd sales agencies and through the company sales performance in Kota Kinabalu Sabah that the researcher chooses in order to attain more information and insight about this research study. To achieve the objective of this study the researcher will provide a questionnaire mainly on personality and separate the questionnaire based on sales agency. Each of the sales agency will provide their sales performance which will be used to measure the relativeness of their salesmanship personality and the sales performance. The outcome for this study could give enhancing information for the company where they may understand and to know which sales agency are the most to be preferred based on their salesmanship personality which offer a good sales performance and can generate more profit to the company. Two types of data collection is used in the research which are primary and secondary data. Primary data is based on information collection form distribution of questionnaire and the secondary data is based on the material availability from the company itself, the internet or other sources of material that are related to this study.